Implementasi Social Responsibility Di Desa Waru Barat Kecamatan Waru, Pamekasan - Imamah, Nur; Hotimah, Nur; Aizah, Aizah; Asis, Abd (STAI Publisistik Thawalib Jakarta, 2022)
Community service activities in Waru Barat village have provided benefits to the community, especially in an effort to provide understanding to people who are still not aware of the importence of social values in the society and a clean lifestyle with several activities that have been carried out. Training and counseling with an overall level of achievement has provided additional knowledge to the community in an effort to support an existence that is based on social values. In general, the community service activities went well because the community response was quite good even though at first they were indifferent to the existence of the service participants. The implementation of these service programs is expected to be useful for the community to have a better understanding of the social personality of the community, and to be able to optimize resources to practice and take advantage of existing opportunities as well as possible.